2015
DOI: 10.1002/iid3.53
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of CD16+CD14dim monocytes increases with tumor cell load in bone marrow of patients with multiple myeloma

Abstract: Multiple myeloma is an incurable cancer with expansion of malignant plasma cells in the bone marrow. Previous studies have shown that monocytes and macrophages in the bone marrow milieu are important for tumor growth and may play a role in the drug response. We therefore characterized monocytes in bone marrow aspirates by flow cytometry. We found that there was significant correlation between the proportion of CX3CR1+, CD16+CD14dim non classical monocytes, and percent plasma cells (PC) in the bone marrow of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…2j, l) which is in line with a previous report. 4 We also observed a significant correlation between the absolute number of Slan-DCs (Spearman r 2 D 0.37, p D 0.0058) but not between Intermediate Monocytes and CD138C cells (Spearman r 2 D 0.04, p D 0.3893) in the BM of responding patients (data not shown). Altogether, these results suggest that circulating Slan-DCs decrease in the PB while intermediate monocytes accumulate in the BM during the MGUS-to-MM progression, and that this accumulation is proportional to the extent of tumor burden.…”
Section: Slan-dcs Are Decreased In MM Patients' Pb While Intermediatementioning
confidence: 63%
See 2 more Smart Citations
“…2j, l) which is in line with a previous report. 4 We also observed a significant correlation between the absolute number of Slan-DCs (Spearman r 2 D 0.37, p D 0.0058) but not between Intermediate Monocytes and CD138C cells (Spearman r 2 D 0.04, p D 0.3893) in the BM of responding patients (data not shown). Altogether, these results suggest that circulating Slan-DCs decrease in the PB while intermediate monocytes accumulate in the BM during the MGUS-to-MM progression, and that this accumulation is proportional to the extent of tumor burden.…”
Section: Slan-dcs Are Decreased In MM Patients' Pb While Intermediatementioning
confidence: 63%
“…3 These M2 TAMs have been shown to accumulate in MM patients bone marrow and this accumulation is associated with poorer survival. 4 Human peripheral blood (PB) monocytes can be classified into three distinct populations: classical CD16-CD14C, intermediate CD16C CD14C and non-classical CD16C CD14-monocytes. 5 Recent reports showed that the proportion of nonclassical monocytes increases with tumor cell load in the BM of MM patients, 4 and that these monocytes can be a potential cytological marker of osteoclast precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDSCs; see [369]). Quantitative and qualitative monocyte defects have been reported, including the reduced release of proinflammatory cytokines [378][379][380][381][382][383][384][385][386].…”
Section: Functional Effects Of Imids Mediated Via Cereblonmentioning
confidence: 99%
“…CD16 + bone marrow monocytes in myeloma patients have distinct features compared with smouldering myeloma and MGUS patients; they overexpress IL21R, which may induce osteoclastic differentiation[159,383,385]. Activin A is a TGF-β cytokine that stimulates osteoclastogenesis; it is derived from bone marrow monocytes and mediates the osteoclastogenic effect of IL-3 in myeloma.…”
mentioning
confidence: 99%